Crop domestication disrupts a native tritrophic interaction associated with the sunflower, Helianthus annuus (Asterales: Asteraceae) - Chen, Yolanda H.; Welter, Stephen C. (Wiley, 2005)
1. Crop domestication has been a largely overlooked factor that may explain why insect herbivores tend to be more abundant and less attacked in agricultural habitats than in native habitats. This study explores how domestication of the sunflower, Helianthus annuus L., affects the sunflower moth, Homoeosoma electellum (Lepidoptera: Pyralidae), and its parasitoids.2. Common garden experiments were used to assess the effect of domestication on larval abundance in an agricultural and a native habitat. The effect of domestication on parasitism was determined using two studies: one study that manipulated nitrogen according to levels found in agricultural and native habitats, and a second common garden study in the native habitat.3. At peak infestation in the agricultural common garden, larval abundance was 10 times higher on agricultural plants than on wild plants. In contrast, larval abundance did not differ between plant genotypes in the native habitat.4. Larvae were four times more likely to be parasitised on wild sunflowers than on agricultural sunflowers, and three times more likely to be parasitised on low nitrogen plants than on high nitrogen plants. Parasitism did not differ between agricultural and wild plants in the native habitat, where flowers were more similar in size.5. Sunflower domestication has increased larval abundance, accelerated larval development, and lowered parasitism. The magnitude of the effect appears to depend upon nutrient availability. Thus, domestication can disrupt tritrophic interactions, and may help explain why some insect pests are more abundant and less attacked in agro‐ecosystems.